Systemic sclerosis - the dermatological perspective - Sticherling, Michael (Journal der Deutschen Dermatologischen Gesellschaft, 2019)
Systemic scleroderma/systemic sclerosis (SSc) is an inflammatory connective tissue disease clinically characterized by two major subtypes: limited and diffuse SSc. While both conditions present with Raynaud's phenomenon (paroxysmal digital ischemia), diffuse SSc is associated with rapid disease progression and early - prognostically relevant - involvement of internal organs. Treatment is challenging. In addition to general lifestyle modifications, measures include treatments aimed at improving circulation as well as immunosuppressive and immunomodulatory drugs. However, these agents are effective only in terms of slowing disease progression.
CRIS-Team WoS Importer:2019-08-13